LITERASI DIGITAL MODERASI BERAGAMA MAHASISWA UIN K.H. SAIFUDDIN ZUHRI PURWOKERTO - Haniati, Umi; Adelia, Nisa; Winastwan, Rheza Ega (IAIN Ponorogo, 2024)
Abstract: The development of technology and information in the current era has brought many influences on human life. Often found on social media, conflicts between communities debate religious diversity in Indonesia. Researchers want to know about the Digital Literacy of Religious Moderation of UIN Students Prof. K.H. Saifuddin Zuhri Purwokerto. The research method used is quantitative descriptive. The research population was undergraduate students, while the research sample was 266. Based on the data processed in the questionnaire distributed, it is known that the digital literacy ability of UIN students Prof. K.H. Saifuddin Zuhri Purwokerto is quite good in various aspects of digital literacy, there is still room for improvement, especially in terms of creativity in composing messages, active participation in social actions, and the ability to collaborate with various parties. This research is expected to be an input for the development of effective learning strategies in improving the digital literacy of religious moderation through the lecture curriculum and the Center for the Study of Religious Moderation and Pancasila at UIN Prof. K.H. Saifuddin Zuhri Purwokerto can be more active in socializing to students in the form of digital literacy of religious moderation.